Analisa Koordinasi Setting Proteksi Over Current Relay (OCR) Outgoing 20 kV dan Recloser pada Trafo II 60 MVA Feeder RBG 01 di Gardu Induk 150 kV Rembang - Safitri, Indri; Gunawan, Gunawan; Nugroho, Agus Adhi (Universitas Semarang, 2020)
According to energy observers from the Institute for Essential Services Reform (IESR) the number of electricity consumers in Indonesia has increased by an average of 6-7% annually followed by an increase in the area of its services. An increasingly broad network is directly proportional to the potential for interference with the transmission and distribution system. The 150 KV Rembang substations is part of the Java-Bali Interconnection electrical system in northern Central Java that supplies electricity to the Rembang and surrounding areas. Rembang 150 KV substation on May 24, 2019, RBG 01 feeder experienced a disturbance behind the RB1-32 recloser and it was recorded that in 2019 PMT it had been tripped 4 times. Besides, there has been a change in equipment in the form of transformer II. These problems indicate the potential for interference that is not anticipated by the protection system, namely Over Current Relay and recloser. This study evaluates the setting of an outgoing 20 KV OCR protections and recloser on transformer II RBG 01 feeder Rembang 150 KV substation. The scenarios used are calculations with large variations of short-circuit current based on% distance, as well as the calculation of OCR and recloser settings with IEC 60255 standards. Setting currents in the protection equipment is regulated based on current conductivity (KHA) and load current on the recloser. The coordination of the protection settings resulting from this resetting will be compared to the conditions on the ground. Existing (field) OCR outgoing feeder RBG 01 condition TMS OCR value = 0.228 seconds, Iset = 480 A, and t op = 0.3 seconds. The existing OCR recloser condition TMS OCR value = 0.120 seconds and Iset = 400 A. The results of OCR coordinating outgoing feeder RBG 01 obtained TMS OCR value = 0.135 seconds, Iset = 585 A, and t operation = 0.3 seconds. OCR recloser resetting conditions obtained TMS OCR value = 0.10 seconds, Iset = 240 A and t operation = 0.198 seconds. The resetting conditions have met the IEC 60255 standard because recloser working time is smaller than outgoing work time.